Getting Technologies to Farmers -- Fixing Regulatory Systems for Agricultural Technologies - Chambers, Judith (2014)
Panel Presentation: Getting Technologies to Farmers -- Fixing Regulatory Systems for Agricultural Technologies by Judith Chambers, Ph.D., Director – Program for Biosafety Systems at IFPRI. Presented at Food Security in a World of Growing Natural Resource Scarcity event February 12, 2014.